Aquatic Environment and Nitrogen and Phosphorus Balance in Micropterus salmoides Culture Under Biofloc Model - Yuqin JIN; Shunlong MENG; Huimin XU; Chao SONG; Limin FAN; Liping QIU; Dandan LI (Progress in Fishery Sciences)
According to the United Nations, the global population is expected to grow by another 2 billion to reach 9.7 billion by 2050. The food production sector faces a great challenge in meeting the growing demand for food with limited land. In this regard, aquaculture may play a key role in maximizing the use of various aquatic resources to produce a wide range of food organisms using a combination of intensive farming practices. However, intensive and semi-intensive Chinese aquaculture practices have led to problems such as water quality decline, disease outbreaks, and environmental degradation, hindering the sustainability of the industry. To address the conservation and biofloc technology has emerged as an eco-friendly solution that maintains water quality, supports environmental conservation, and facilitates material cycling.Excessive feed and fertilizer addition in aquaculture activities results in an undesirable buildup of nitrogen and phosphorus within the aquaculture system. This accumulation not only degrades the water quality and surrounding environment, but also facilitates the spread of numerous pathogens, posing a significant threat to aquaculture organisms. To mitigate this issue, it is crucial to assess the nitrogen and phosphorus budget in aquaculture systems, tracing the sources and destinations of these nutrients. By quantifying the inputs and outputs of nitrogen and phosphorus, we can gain insights into their utilization efficiency within the system. This understanding is vital for enhancing water quality, minimizing ecological pollution, optimizing feed utilization by aquaculture organisms, and ultimately promoting the sustainable development of the aquaculture industry. While the nitrogen and phosphorus balance of various cultured organisms in diverse aquaculture systems has been extensively explored, a gap in knowledge regarding the nitrogen and phosphorus balance in the Micropterus salmoides biofloc technology culture models remain. Additionally, there is a need for systematic monitoring and collection of pertinent data to fill this gap in knowledge.To investigate the aquatic environment and nitrogen and phosphorus balance of M. salmoides under the biofloc model, an experiment was conducted in 300 L glass tank. The experiment comprised of a blank group, which was fed a basal diet, and a biofloc group, where glucose was added to maintain a C/N ratio of 15. Each group had three parallel setups, with a stocking density of 20 tails per tank. The experiment ran for 60 days, employing a zero-water exchange aquaculture mode. The results revealed a significant reduction (P < 0.05) in NH4+-N, NO2–-N, NO3–-N, TN, and TP levels in the water body of the biofloc group compared to that of the blank group, with reductions of 57.07%, 80.22%, 30.50%, 24.64%, and 31.47%, respectively. The results showed that feed was the main source of nitrogen and phosphorus in the blank and biofloc groups, contributing (90.60±0.08)% and (96.08±0.19)% in the blank group, and (87.16±0.19)% and (92.30±0.24)% in the biofloc group, respectively. The main output of nitrogen was harvesting of M. salmoides, which accounted for (43.04±1.42)% of the input nitrogen in the blank group and (44.17±1.53)% of that in the biofloc group, respectively. Sediment accumulation was the main pathway of phosphorus export from the culture system, which accounted for (75.92±0.47)% of the input phosphorus in the blank group and (74.70±0.71)% of that in the biofloc group, respectively. The absolute and relative utilization rates of nitrogen in the biofloc group were (44.17±1.53)% and (50.69±1.87)%, respectively, which were higher than those of the blank group (43.04±1.42)% and (47.51±1.60)%; however, none of the differences were significant (P > 0.05); whereas the absolute and relative utilization rates of phosphorus in the biofloc group were (17.41±0.14)% and (18.87±0.20)%, respectively, which were significantly higher than (13.06±0.36)% and (13.59±0.38)% in the blank group (P < 0.05).These results indicate that the biofloc model of M. salmoides culture can regulate the aquaculture water quality, reduce nitrogen and phosphorus accumulation, and improve nitrogen and phosphorus utilization efficiency by aquaculture organisms with ecological benefits, which is crucial for promoting the healthy and green development of aquaculture in China.